Retraction: Food and social background of nasopharyngeal cancer patients in Jakarta (Medical Journal of Indonesia, 1998)
The Editorial Board wishes to apologize for publishing the following article in the Medical Journal of Indonesia, vol. 6 # 4, October-December 1997 edition. "Food and social background of nasopharyngeal cancer patients in Jakarta" by A. Roezin. This article is a duplication of an article written by the same author under the same title, published in the Asean Otolaryngology-Head and Neck Surgery Journal vol.1 # 1, January-March 1997 edition.